Peningkatan Pencapaian Nilai Akreditasi Pelayanan Rekam Medis Rumah Sakit Lancang Kuning Pekanbaru Tahun 201 - Henny Maria Ulfa (STIKes Hang Tuah Pekanbaru, 2012)
In an effort to improve the quality of care, the hospital must conduct periodic accreditation at least every three years. Standard hospital services meet five basic service activities, namely administration and management, medical services, emergency services, nursing services, medical record services and each hospital has a duty to carry medical records. Preliminary data indicate that the assessment parameter passing grade accreditation service medical records are lacking. The purpose of this study to find out how to increase the value of the parameter Hospital medical service record Lancang Kuning Pekanbaru minimum national standards. This type of research is non standard qualitative data collection methods of observation and in-depth interviews with four informants. Data processing is done by using the technique of triangulation and qualitative analysis. The result showed that the measurement of medical record services performed according to the standard one to seven is only 25.45%. According to the Ministry of Health of the Republic of Indonesia Year 2008 that the value is still below 75%, so the lack of adherence to accreditation standards, therefore, necessary guidelines in accordance with the standard of care medical record up to seven to improve the assessment of medical record services. Lancang Kuning Hospital Pekanbaru after the implementation of the service records of only six standards that could be applied but still not achieve a passing grade of accreditation of medical record services. Caused by power unit medical record does not meet the qualifications of office, the room is not in accordance with the standards of the medical records due to lack of funding from the hospital. Suggested to the hospital for a complete medical record service standards accreditation standards in order to achieve maximum value assessment result therefore hospitals need to create programs and activities, obey the Law of the Republic of Indonesia hospital, and perform periodic accreditation minimum three years if no longer meets the requirements and standards of the hospital license can be revoked.